2018
DOI: 10.1111/1750-3841.14068
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Kombucha Tea Fermentation: A Review

Abstract: Abstract:Kombucha is a beverage of probable Manchurian origins obtained from fermented tea by a microbial consortium composed of several bacteria and yeasts. This mixed consortium forms a powerful symbiosis capable of inhibiting the growth of potentially contaminating bacteria. The fermentation process also leads to the formation of a polymeric cellulose pellicle due to the activity of certain strains of Acetobacter sp. The tea fermentation process by the microbial consortium was able to show an increase in ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
344
0
44

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 405 publications
(394 citation statements)
references
References 70 publications
6
344
0
44
Order By: Relevance
“…However, it has also been reported that this species has potential beneficial characteristics for fermented foods (Ciani, Comitini, Mannazzu, & Domizio, 2010;Jolly, Augustyn, & Pretorius, 2017;Kuanyshev et al, 2017;Xu, Zhi, Wu, Du, & Xu, 2017). Also, it is one of the most commonly reported yeast genera in Kombucha microbiome studies (Jayabalan et al, 2014;Marsh et al, 2014;Villarreal-Soto, Beaufort, Bouajila, Souchard, & Taillandier, 2018). Despite the recent genomic-based studies, the role of Zygosaccharomyces in fermented foods and its potential effects have not yet been elucidated in detail (Kuanyshev et al, 2017).…”
Section: Reconstruction Of Individual Dominant Genomesmentioning
confidence: 99%
“…However, it has also been reported that this species has potential beneficial characteristics for fermented foods (Ciani, Comitini, Mannazzu, & Domizio, 2010;Jolly, Augustyn, & Pretorius, 2017;Kuanyshev et al, 2017;Xu, Zhi, Wu, Du, & Xu, 2017). Also, it is one of the most commonly reported yeast genera in Kombucha microbiome studies (Jayabalan et al, 2014;Marsh et al, 2014;Villarreal-Soto, Beaufort, Bouajila, Souchard, & Taillandier, 2018). Despite the recent genomic-based studies, the role of Zygosaccharomyces in fermented foods and its potential effects have not yet been elucidated in detail (Kuanyshev et al, 2017).…”
Section: Reconstruction Of Individual Dominant Genomesmentioning
confidence: 99%
“…KMC is well known as the producer of a popular soft drink (kombucha tea), commercially available and claimed to be beneficial for human health ( Jayabalan et al, 2014;V ına et al, 2014;Villarreal-Soto et al, 2018). We have been able to brew kombucha tea from cultures that have 192 PODOLICH ET AL.…”
Section: Morphology and Activity Of Revived Kombucha Community Membersmentioning
confidence: 99%
“…There is a small body of literature in which various microbiological and biochemical analyses of kombucha have been published (see [2] for a recent review), but we are aware of only one publication about kombucha in the chemical education literature [5]. In studies of green and black tea kombucha that we prepared, we observed that during one month of fermentation the sucrose concentration decreases steadily as it is broken down by invertase, and the glucose and fructose concentrations each increase concomitantly.…”
Section: Introductionmentioning
confidence: 92%